Five-Year Follow-up of Minimally Invasive Distal Metatarsal Chevron Osteotomy in Comparison with the Open Technique: A Randomized Controlled Trial. (20th May 2020) - Kaufmann, Gerhard; Mörtlbauer, Lorenz; Hofer-Picout, Philipp; Dammerer, Dietmar; Ban, Michael; Liebensteiner, Michael
Abstract : Background: The aim of the present prospective randomized study was to evaluate the long-term outcomes of minimally invasive chevron osteotomy as compared with open distal chevron osteotomy for the correction of hallux valgus deformity. Methods: A randomized controlled design was applied. The following parameters were assessed at 6 and 12 weeks, 9 months, and 5 years postoperatively: the American Orthopaedic Foot & Ankle Society (AOFAS) Forefoot Score, a visual analog scale (VAS) score for pain, and a patient-satisfaction score. In addition, several radiographic parameters for hallux valgus correction and joint degeneration were collected. Range of motion was also assessed. Thirty-nine of 47 feet were available for analysis at the time of the latest follow-up. Results: During the 5-year study period, the outcomes of the minimally invasive technique were comparable with those of the open technique. No significant differences were seen between the 2 groups within 5 years postoperatively in terms of clinical outcomes (VAS, AOFAS, satisfaction), radiographic outcomes, joint degeneration, or range of motion. Conclusions: Five years after treatment, the outcome following minimally invasive distal chevron osteotomy is comparable with that for the open technique for hallux valgus surgery. Levels of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.